Biodegradable m-PEG/PCL Core-Shell Micelles: Preparation and Characterization as a Sustained Release Formulation for Curcumin - Hossein Danafar; Soodabeh Davaran; Kobra Rostamizadeh; Hadi Valizadeh; Mehrdad Hamidi (Tabriz University of Medical Sciences, 2014)
Purpose: Among the potent anticancer agents, curcumin is known as a very efficacious against many different types of cancer cells, but its clinical applications has been limited because of hydrophobicity, low gastrointestinal absorption, poor bioavailability and rapid metabolism. In this way, a novel micellar delivery system with mPEG-PCL was synthesized and the release profile of the curcumin from the drug-loaded micelles was evaluated. Methods: In this study, curcumin was encapsulated within monomethoxypoly(ethylene glycol)-poly(ε-caprolactone) (mPEG-PCL) micelles through a single-step nano-precipitation method, leading to creation of curcumin-loaded mPEG-PCL (Cur/mPEG-PCL) micelles. Di-block mPEG-PCL copolymers were synthesized and used to prepare micelles. mPEG-PCL copolymer was characterized in vitro by HNMR, FTIR, DSC and GPC techniques. Then, mPEG-PCL copolymers with curcumin were self-assembled into micelles in aqueous solution. The resulting micelles were characterized further by various techniques such as dynamic light scattering (DLS) and atomic force microscopy (AFM). Results: The findings showed the successful formation of smooth and spherical curcumin-loaded micelles. The encapsulation efficiency of curcumin was 88 ± 3.32%. The results of AFM revealed that the micelles have spherical shapes with size of 73.8 nm. The release behavior of curcumin from micelles was compared in different media. In vitro release of curcumin from curcumin-entrapped micelles was followed remarkably sustained profile. The sustained release of drug was hypothetically due to the entrapment of curcumin in core of micelles. Conclusion: The results indicate the successful formulation of curcumin loaded m-PEG/PCL micelles. From the results, iIt can be concluded that curcumin m-PEG-PCL micelles may be considered as an effective treatment strategy for cancer in the future.